2013
DOI: 10.1021/jo401232a
|View full text |Cite
|
Sign up to set email alerts
|

Calix[2]thia[4]phyrin: An Expanded Calixphyrin with Aggregation-Induced Enhanced Emission and Anion Receptor Properties

Abstract: The synthesis of calix[2]thia[4]phyrin 3, a core-modified expanded calixphyrin, by an efficient synthetic route is reported. 3 exhibits an aggregation-induced enhanced emission (AIEE) phenomenon upon addition of increasing amounts of water. This is attributed to the restricted intramolecular rotation of the meso-aryl rings present on the sp(3) bridging carbons. SEM studies revealed the formation of aggregation in an acetonitrile/water mixture with an average diameter of the aggregate in the range 0.38-2.08 μm.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 38 publications
0
14
0
1
Order By: Relevance
“…32 Another example of the ability for hydrogen bonds to direct crystal structures was found by Chandrashekar and co-workers. 33 The authors observed by X-ray crystallography the formation of a supramolecular assembly of calixphyrins held by intermolecular C-H Nath and Baruah studied the crystal structures of two fluorine-substituted bis-phenols. 34 Depending on the solvent used for the crystallization of bis-phenol 13 ( Figure 12), one of two polymorphs can be obtained.…”
Section: Short Review Syn Thesismentioning
confidence: 99%
“…32 Another example of the ability for hydrogen bonds to direct crystal structures was found by Chandrashekar and co-workers. 33 The authors observed by X-ray crystallography the formation of a supramolecular assembly of calixphyrins held by intermolecular C-H Nath and Baruah studied the crystal structures of two fluorine-substituted bis-phenols. 34 Depending on the solvent used for the crystallization of bis-phenol 13 ( Figure 12), one of two polymorphs can be obtained.…”
Section: Short Review Syn Thesismentioning
confidence: 99%
“…However, the anion sensing properties of these macrocycles have not been studied. 8 A perusal of the literature revealed that the reports on core-modified expanded calixphyrins 9 are very scarce to understand their complete potential for anion sensing applications. In 1999, Chandrashekar and coworkers 10 reported first stable core-modified meso-aryl smaragdyrins such as 5,10,19-triphenyl-25-oxasmaragdyrin 1a and 5,10,19-triphenyl-25-thiasmaragdyrin 1b (Scheme 1) which contain four pyrrole rings and one furan/thiophene ring that are connected via three methine bridges and two direct bonds.…”
Section: Introductionmentioning
confidence: 99%
“…The macrocycles 3a-c were prepared by condensing one equivalent of 4 with one equivalent of appropriate dipyrromethane 5 in CH 2 Cl 2 in the presence of 0.1 equivalent of TFA under a N 2 atmosphere at room temperature for 1 h followed by oxidation with DDQ in air for additional 1 h. TLC analysis showed mainly one major red spot and absorption spectroscopy showed one broad band at ∼450 nm indicating the formation of a macrocycle. 7,[13][14][15][23][24][25][26][27][28] The crude compound was subjected to alumina column chromatography and afforded the macrocycles 3a-c as orange red solids in 16-19% yields. Although we expected the formation of an expanded macrocycle containing one meso-sp 3 carbon such as compound 6 (Scheme 1), the X-ray structure of one of the macrocycles and detailed NMR studies indicated the formation of an expanded dithiacalixphyrin having two meso sp 3 carbons such as macrocycles 3a-c.…”
Section: Resultsmentioning
confidence: 99%